Paternal and maternal transition to parenthood: the risk of postpartum depression and parenting stress - Maria Stella Epifanio; Vitalba Genna; Caterina De Luca; Michele Roccella; Sabina La Grutta (MDPI AG, 2015)
Transition to parenthood represents an important life event increasing vulnerability to psychological disorders. Postpartum depression and parenting distress are the most common psychological disturbances and a growing scientific evidence suggests that both mothers and fathers are involved in this developmental crisis. This paper aims to explore maternal and paternal experience of transition to parenthood in terms of parenting distress and risk of postpartum depression. Seventy-five couples of first-time parents were invited to compile the Edinburgh Postnatal Depression Scale and the Parenting Stress Index-Short Form in the first month of children life. Study sample reported very high levels of parenting distress and a risk of postpartum depression in 20.8% of mothers and 5.7% of fathers. No significant correlation between parenting distress and the risk of postpartum depression emerged, both in mothers than in fathers group while maternal distress levels are related to paternal one. The first month after partum represents a critical phase of parents life and it could be considered a developmental crisis characterized by anxiety, stress and mood alterations that could have important repercussions on the child psycho-physical development.